2020
DOI: 10.1080/02678373.2020.1832607
|View full text |Cite
|
Sign up to set email alerts
|

The ups and downs of felt job insecurity and job performance: The moderating role of informational justice

Abstract: with details of the nature of the infringement. We will investigate the claim and if justified, we will take the appropriate steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…et al, 2006;Zapata-Phelan et al, 2009). Informational justice has only rarely been investigated in relation to performance (Schumacher et al, 2020), however the combined dimension of interactional justice (interpersonal and informational justice) has shown promising support for a positive relationship with task performance (Zapata-Phelan et al, 2009). This shows that whilst various studies have consistently found support for the overall relationship between organizational justice and performance (Unterhitzenberger and Bryde, 2019;Mahajan and Benson, 2013;Swalhi et al, 2017), the impact of the individual dimensions is less clear.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…et al, 2006;Zapata-Phelan et al, 2009). Informational justice has only rarely been investigated in relation to performance (Schumacher et al, 2020), however the combined dimension of interactional justice (interpersonal and informational justice) has shown promising support for a positive relationship with task performance (Zapata-Phelan et al, 2009). This shows that whilst various studies have consistently found support for the overall relationship between organizational justice and performance (Unterhitzenberger and Bryde, 2019;Mahajan and Benson, 2013;Swalhi et al, 2017), the impact of the individual dimensions is less clear.…”
Section: Hypothesesmentioning
confidence: 99%
“…The picture is similarly contradicting for the association between interpersonal justice and task performance, as some studies found significant support for the relationship (Cropanzano et al, 2002; Rupp & Cropanzano, 2002), whereas others did not (Colquitt et al, 2006; Zapata-Phelan et al, 2009). Informational justice has rarely been investigated in relation to performance (Schumacher et al, 2020); however, the combined dimensions of interactional justice (interpersonal and informational justice) have shown promising support for a positive relationship with task performance (Zapata-Phelan et al, 2009). This shows that, although various studies have consistently found support for the overall relationship between organizational justice and performance (Mahajan & Benson, 2013; Swalhi et al, 2017; Unterhitzenberger & Bryde, 2019) the impact of the individual dimensions is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…This component of organizational justice can balance the resources lost as a consequence of job insecurity. Schumacher et al (2020) examined how job insecurity relates to job performance based on the Conservation of Resources theory. The authors assumed a reduced impact of job insecurity on employees’ performance when exposed to greater levels of informational justice.…”
Section: Introductionmentioning
confidence: 99%
“…First, employees experiencing job insecurity have strong intentions to protect their job opportunities, which are valuable resources to them [ 16 , 25 ]. Hence, they will pay more attention and energy to activities that help them maintain employment relationships [ 26 ]. For instance, employees may put effort into specific work to increase their performance in the short run.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%